Memahami Pilihan Skincare Lokal Gen Z Melalui Reputasi dan Citra Toko: Sebuah Studi Kasus di Jabodetabek - Suresh Kumar (Lentera Ilmu Madani, 2025)
This study examines how corporate reputation and store image influence Generation Z’s choices of local skincare products in Greater Jakarta, with trust and perceived risk as central considerations. Using a qualitative case study design, data were collected through semi-structured interviews with 15 Gen Z consumers who had purchased local skincare products within the last six months. Thematic analysis revealed four major themes: reputation as a trust signal, store image and the retail experience, trust and risk in skincare choices, and Gen Z’s hybrid decision-making process. Findings indicate that reputation, particularly when reinforced by halal certification and influencer visibility, enhances trust, while a positive store image—through clean layouts, organized displays, and social-media-friendly atmospheres—reduces perceived risk. Trust emerged as the mediator linking reputation and store image to purchase decisions, whereas perceived risk continued to function as a barrier when product authenticity was uncertain. Importantly, Gen Z consumers blended online validation (e.g., TikTok reviews, peer opinions) with offline store experiences, creating a unique hybrid pathway to decision-making. The study contributes to the literature by offering qualitative evidence on the interaction of intangible brand cues in the Indonesian skincare context and provides practical recommendations for local brands to strengthen reputation, curate credible store images, minimize perceived risk, and integrate online and offline strategies to appeal to Gen Z consumers.